Diversity analysis of moray eel (muraenidae) on artificial reef structure in mengiat beach, Nusa Dua, Bali - Nathanael Wilbert; Husna Nugrahapraja (Environmental and Materials, 2023)
Optimal coral growth has a positive impact on increasing biodiversity. This can be observed through the increase in the number of marine species as the transplanted coral reefs age. One natural indicator in coastal ecosystems is the presence of moray eels. Within the coral reef ecosystem, the diversity of moray eels as natural predators belonging to the category of reef fish can serve as an indication of a healthy and balanced ecosystem. The method used in this research is visual counting or visual observation of several species of marine eels on three different major installed reef star media, as part of coral reef restoration efforts. The data collection locations include three points of reef star media installation: BTN, Coral Garden, and Cluster 5. The water conditions in these locations, such as salinity, temperature, pH, and conductivity, indicate the adequate quality to support coral reef restoration efforts. In this study, five species of marine eels frequently encountered in the three data collection locations identified as: Echidna nebulosa, Gymnothorax thyrsoideus, Gymnothorax fimbriatus, Gymnothorax pictus, and Gymnothorax richardsonii. The highest abundance and diversity were found in Coral Garden, followed by Cluster 5, with BTN being the lowest.